Cytogenetic analysis of 179 Iranian women with premature ovarian failure. (June 2013) - Kalantari, Hamid; Madani, Tahereh; Zari Moradi, Shabnam; Mansouri, Zahra; Almadani, Navid; Gourabi, Hamid; Mohseni Meybodi, Anahita
Abstract The importance of chromosomal abnormalities in etiology of premature ovarian failure (POF) is well known but in many cases, POF still remains idiopathic. We investigated the frequency and type of chromosomal aberrations in Iranian women diagnosed with idiopathic POF. Standard cytogenetic analysis was carried out in a total of 179 patients. Karyotype analysis of these patients revealed that 161 (89.95%) patients had normal female karyotype and 18 (10.05%) patients had abnormal karyotypes. The abnormal karyotypes included sex reverse sex determining region Y (SRY) negative (five Cases), X chromosome mosaicism (five cases), abnormal X chromosomes (three cases), abnormal autosomes (three cases) and X-autosome translocation (two cases). The overall prevalence of chromosomal abnormalities was 10.05% in this first large-scale report of chromosomal aberrations in Iranian women with POF. The results confirm previous observations and emphasis on the critical role of X chromosome abnormalities as one of the possible etiologies for POF.